Dexamethasone Cyclophosphamide Pulse Therapy in Dermatology - Parajuli, S; Paudel, U; Pokhrel, DB (Journal of Institute of Medicine Nepal, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Introduction: The objectives of this study was to: study profile of dermatological disease treated with pulse therapy in TUTH , determine the clinical time to remission of diseases, duration of remission after withdrawal of treatment and determine the side effect profile of the treatment. Materials and Methods: Demographic profile of the patients treated with pulse therapy for various dermatological conditions, the duration of diseases prior to treatment, the clinical time to remission of diseases, duration of remission after withdrawal of treatment and side effects of treatment. Results: Pulse therapy was received by 12 patients, five patients were SLE (F: M-4:1) with mean age of onset 28.75yrs, six patients were of Pemphigus (F: M-1:1) with mean age of onset 30.6 yrs and there was one 40 yrs old female patient of scleromyxoedema. The mean duration of disease prior to treatment was 2.8 yrs in SLE and 1.4 yrs in Pemphigus. The mean duration of clinical time to remission was 4 months for SLE while only one patient of Pemphigus had received clinical remission after 6 months. Duration of remission after withdrawal of treatment could not be ascertained because none of them had completed phase III. The main side effects observed in our study were flushing and secondary infection. Conclusion: DC pulse therapy appears to be encouraging treatment in the treatment of dermatological conditions like SLE, Pemphigus and scleromyxoedema. However study involving a large number of patient and long duration of follow up is needed before considering it as best treatment available for treatment of these conditions. Key word: Dexamethasone cyclophsophamide pulse; Pemphigus; SLE; Scleromyxoedema Journal of Institute of Medicine, April, 2008; 30:1 51-54 The full text of this paper is available from the Journal of Institute of Medicine website